Dampak Program Pembelajaran Daring di SD Muhammadiyah I Borobudur pada Masa Pandemi : Prestasi Belajar - Hani Fitria Sari (Prosiding University Research Colloquium, 2021)
This study aims to find out how the teacher's efforts to improve student achievementduring the pandemic. Because during a pandemic like this, learning activities take placedifferently than usual, namely through online learning that utilizes gadget technology.While learning usually takes place offline or face to face. The research method used isdescriptive qualitative research method. Data collection techniques using observation andinterviews. From the results of the study, it can be seen that the efforts made by theteacher are good, but there are several factors that become problems for students and areconstrained by other things. This study aims to determine the impact of online learning inthe context of student achievement.